Computer-assisted everything? Tools and techniques for design and production. - ALIC, John A. (1995)
Discusses applications of computer-assisted technologies in both product design/development and manufacturing in order to explore the capabilities - andlimits - of computer-automated engineering and manufacturing. Examines the impact on international competitiveness.